Using a community of practice model to create change for Northern homeless women - Poole, Nancy; Bopp, Judie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
This is a story about three virtual and face-to-face communities which met in the capitals of Canada’s three Northern territorial cities over a two-year period to discuss and act on culturally safe and gender-specific services for Northern women (and their children) experiencing homelessness, mental health and substance use concerns. It is a story of how researchers and community-based advocates can work across distance and culture, using co-learning in virtual communities as a core strategy to create relational system change. The three communities of practice were linked through a pan-territorial action research project entitled Repairing the Holes in the Net, in which all participants: learned together, mapped available services, discussed the findings from interviews with northern women about their trajectories of homelessness, analyzed relevant policy, planned local service enhancements, and generally took inspiration from each other.